METALLOGENIC PROVINCE DERIVED FROM MANTLE SOURCES: ND, SR, S AND PB ISOTOPE EVIDENCE FROM THE CENTRAL ASIAN OROGENIC BELT - Hong D.; Zhang J.; Wang T.; Wang S.; Xie X. (My University, 2003)
The Central Asian Orogenic Belt (CAOB) is one of the most important regions for Cu, Au and polymetallic and rare metallic (Li, Be, Nb, Ta) mineralization over the world. Most of the ore deposits in the CAOB are closely associated with granitoids. Available Sr, Nd, S and Pb isotopic data indicate that the metallogenic epoch and sources of the mineral deposits in the CAOB are consistent with that of the regional granites. Available data suggest that mantle sources could have played an important role in the Paleozoic to Mesozoic mineralization in the CAOB.
Keywords: Central Asian Orogenic Belt; metallogenic province; mantle source; Sr; Nd; S and Pb isotopes